Um método heurístico para a resolução de uma classe de problemas de sequenciamento da produção envolvendo penalidades por antecipação e atraso - Kramen, Arthur Harry frederico Ribeiro (2016)
This work proposes a uni ed heuristic algorithm for a large class of earlinesstardiness (E-T) scheduling problems. We consider single/parallel machine E-T problems that may or may not consider some additional features such as idle time, setup times and release dates. In addition, we also consider those problems whose objective is to minimize either the total (average) weighted completion time or the total (average) weighted ow time, which arise as particular cases when the due dates of all jobs are either set to zero or to their associated release dates, respectively. The developed local search based metaheuristic framework is quite simple, but at the same time relies on sophisticated procedures for e ciently performing local search according to the characteristics of the problem. The algorithm was tested in hundreds of instances of several E-T problems and particular cases. The results obtained show that our general heuristic is capable of producing high quality solutions when compared to the best ones available in the literature that were obtained by speci c methods. Moreover, the algorithm was tested on a new set of instances proposed for the most general case (Rjrj ; sk ij jPw0j Ej + wjTj) of the class of problems considered, in order to validate the method.